miR-10a suppresses colorectal cancer metastasis by modulating the epithelial-to-mesenchymal transition and anoikis - Liu, Yankun; Zhang, Yingnan; Wu, Haidong; Li, Yufeng; Zhang, Yi; Liu, Min; Li, Xin; Tang, Hua (Cell death & disease, 2017)
MicroRNAs (miRNAs) have a critical role in tumorigenesis and metastasis, which are major obstacles of cancer therapy. However, the role of miRNAs in colorectal cancer (CRC) metastasis remains poorly understood. Here, we found that miRNA-10a (miR-10a) was upregulated in primary CRC tissues and cell line (SW480) derived from primary CRC compared with metastatic cancer tissues in lymph node and cell line (SW620). The differential expression of miR-10a was inversely correlated with distant metastasis and invasion depth. miR-10a promoted migration and invasion in vitro but inhibited metastasis in vivo by regulating the epithelial-to-mesenchymal transition and anoikis. Furthermore, matrix metalloproteinase 14 (MMP14) and actin gamma 1 (ACTG1) were validated as target genes of miR-10a in CRC cells. Ectopic expression of MMP14 and ACTG1 counteracted the decreased cell adhesion and anoikis resistance activities induced by miR-10a. These findings not only describe the mechanism by which miR-10a suppresses CRC metastasis but also suggest the potential prognostic and therapeutic value of miR-10a in CRC patients.